Factors that Influence the selection of Reservoir Construction Providers using the E-Purchasing Method via Electronic Catalog - Putra, Aditya; Biantoro, Agung Wahyudi (ASTONJADRO, 2025)
The implementation of Electronic Catalog Purchasing in the Construction Sector for Reservoir Development carried out by the DKI Jakarta Provincial Water Resources Service is something new in Indonesia and includes the implementation/utilization of the Risk-Based Construction Sector Catalog, so catalog users need to have adequate technical understanding of the field and be able to mitigate risks. Apart from that, the product specifications and prices displayed by Business Actors are not yet final, therefore, at the purchasing stage a "Correction" process is required by the prospective Buyer (in this case the Commitment Making Officer (PPK)/Procurement Official (PP)) and the selection of the appropriate construction service provider. Using e-purchasing methods is influenced by many factors. So to get a service provider who is competent in carrying out construction contracts, it is hoped that the results of selecting a good provider. This makes budget users need what and dominant factors influence the selection of construction service providers using the e-purchasing method. The research method used is the Quantitative Method by processing the research instrument data in the form of a Questionnaire, then data management is carried out using the Statistical Product and Service Solutions (SPSS) Method for the Questionnaire validity test, Questionnaire reliability test, correlation test, Factor Analysis test and RII (Relative Important Index). ). With the results of the sequence of sub-factors that influence service users in determining the selection of a reservoir construction provider using the E-purchasing method via an electronic catalog, namely: RII: 0.967), and Management of the business entity is not under criminal proceedings (RII: 0.963), 0.958), 0.949) and Variable X1 Administrative Qualification Criteria is the dominant factor variable.